Edukasi Literasi Digital dan Kecakapan Perawat dalam Penggunaan Media Sosial - Yulastri Arif; Zifriyanthi Minanda Putri; M. Hardiansyah; Sasmita Dewi; Marthaliza Simond; Gina Santalia; Mistriana Wahyuni; Sity Halimah; Masyithah Fadhani (Warta Pengabdian Andalas, 2023)
Nurses frequently utilize social media in their professional activities in the digital era. However, there are concerns that some nurses engage in behaviours that breach ethical and legal standards when using social media, potentially impacting patient safety and legal repercussions. One approach to mitigate these impacts is through digital literacy training. This training aims to enhance nurses' knowledge, attitudes, and skills in responsibly utilizing social media for improved patient care. The training was delivered in lectures, simulations, and case studies over 8 hours. A total of 38 nurses participated in this training. After attending the training, the nurses' knowledge scores improved from 24% to 88%. Additionally, their attitudes towards the use of social media showed a positive increase, with 96.4% having a positive attitude post-training. Competence in using social media also improved, from 63.43% to 84.6%. Digital literacy training is vital in enhancing nurses' understanding and proficiency in using social media ethically and responsibly.